Dietary supplementation of lysine and/or methionine on performance, nitrogen retention and excretion in pacu Piaractus mesopotamicus reared in cages - Abimorad, Eduardo Gianini [UNESP]; Favero, Gisele Cristina [UNESP]; Castellani, Daniela [UNESP]; Garcia, Fabiana [UNESP]; Carneiro, Dalton Jose [UNESP] (Elsevier B.V., 2009)
A study was conducted to evaluate the effect of dietary supplementation of lysine and/or methionine on growth performance, nitrogen retention and excretion in pacu juveniles reared in cages. Five diets were prepared; four diets based on plant ingredients containing 23% digestible protein (DP), basal: Lys-and Met-deficient, 23L: basal supplemented with lysine only, 23M: basal supplemented with methionine only, and 23LM: basal supplemented with both amino acids and a protein-bound AAs diet based on fish and soybean meal, containing 30% DP. Survival, specific growth rate, protein efficiency rate and feeding cost were not influenced by the dietary treatments (P>0.05). Fish fed basal diet showed the lowest mean of N retention. Fish fed 30DP diet showed the best results of weight gain(WG) and apparent food conversion rate (FCR) among the dietary treatments. on the other hand, WG in the 23LM group and FCR in the 23LM and 23M groups were not significantly different from the group fed 30DP diet, and showed the highest mean of N retention. There was higher N excretion (P<0.05) when the fish were fed 30DP and 23L diets than the other dietary treatments. Fish fed plant protein-based diets containing 23% DP supplemented with both amino acids or methionine alone showed satisfactory growth and N retention results when compared with fish fed 30DP diet, with the advantage of lower N emissions into water. The results also evidence the pacu's great potential to be reared in cages. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Piaractus mesopotamicus; Digestible amino acids; Growth performance; Nitrogen utilization; N excretion; Feeding cost; Cage